A self-supporting electrode of bamboo-shaped nitrogen-doped carbon nanotube-coated FeCo alloy and a preparation method and application thereof
Patent Information
- Application Number
- CN202611233130.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]发明目的:本发明的目的是针对现有技术中粉体双功能催化剂需依赖聚合物粘结剂涂覆于集流体,导致附加界面阻抗、活性位点遮蔽且催化层在弯折或长循环中易剥离等问题,提供一种竹节状氮掺杂碳纳米管包覆FeCo合金的自支撑电极及其制备方法与应用
[0020]有益效果:(1)氮掺杂碳纳米管直接生长于柔性碳布纤维表面,催化层与集流体形成连续导电的一体化结构。该结构在作为锌-空气电池空气阴极时无需聚合物粘结剂,有利于减少附加界面并保持催化层在弯折状态下的完整性。
Smart Images

Figure CN123017995A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage and conversion technology, and relates to a self-supporting electrode of FeCo alloy coated with bamboo-shaped nitrogen-doped carbon nanotubes, its preparation method and application. Background Technology
[0002] Rechargeable zinc-air batteries are characterized by high theoretical energy density, wide availability of raw materials, and relatively high safety. Flexible zinc-air batteries can also be adapted to wearable electronic devices by bending or fitting curved surfaces, thus requiring simultaneous performance of the air cathode in terms of catalytic activity, conductivity, gas transport capacity, and mechanical integrity.
[0003] Rechargeable zinc-air batteries involve the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) during discharge and charging, respectively. Both reactions exhibit relatively slow kinetics. Pt-based catalysts are typically used to promote ORR, while RuO2 or IrO2 is typically used to promote OER. However, the cost, resource availability, and long-term stability of precious metal materials limit their large-scale application. Therefore, there is a need to develop non-precious metal bifunctional oxygen electrocatalysts that possess both ORR and OER activities.
[0004] Fe, Co, and nitrogen-doped carbon materials can promote oxygen electrocatalytic reactions through the synergistic effect between metal species, nitrogen-containing active sites, and conductive carbon frameworks. Among them, FeCo alloy nanoparticles coated with a nitrogen-containing carbon layer can provide metal active components while slowing down particle migration and aggregation; bamboo-like nitrogen-doped carbon nanotubes can also construct a continuous conductive network and provide open mass transfer channels.
[0005] Existing powdered catalytic materials typically require mixing with conductive agents and polymer binders before coating onto the current collector. This preparation method increases the number of electrode interfaces, the binder may also obscure some active sites, and the catalytic layer may crack or peel off during repeated bending or long-term charge-discharge processes. Therefore, how to directly grow bifunctional oxygen catalytic materials on a flexible conductive substrate while simultaneously obtaining a stable self-supporting structure and a usable catalytic interface is a technical problem that needs to be solved in this field. Summary of the Invention
[0006] Purpose of the invention: The purpose of this invention is to address the problems in the prior art where powder bifunctional catalysts rely on polymer binders to be coated on the current collector, resulting in additional interfacial impedance, shielding of active sites, and easy peeling of the catalyst layer during bending or long cycles. The invention provides a bamboo-shaped nitrogen-doped carbon nanotube-coated FeCo alloy self-supporting electrode, its preparation method, and its application.
[0007] Technical solution: The present invention provides a self-supporting electrode of FeCo alloy coated with nitrogen-doped carbon nanotubes in a bamboo-like structure, comprising a flexible carbon cloth substrate, an array of nitrogen-doped carbon nanotubes grown in situ on the surface of the flexible carbon cloth substrate, and FeCo alloy nanoparticles; the nitrogen-doped carbon nanotubes have a bamboo-like structure, and the FeCo alloy nanoparticles are at least partially encapsulated within the nitrogen-doped carbon nanotubes, and the nitrogen-doped carbon nanotube array and the flexible carbon cloth substrate together form a continuously conductive self-supporting structure.
[0008] Furthermore, at least a portion of the surface of the FeCo alloy nanoparticles is coated with a graphitized carbon shell.
[0009] Furthermore, the electrode contains pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen, and the nitrogen atom content on the electrode surface is 8-15 atoms.
[0010] Another object of the present invention is to provide a method for preparing the above-mentioned bamboo-shaped nitrogen-doped carbon nanotube-coated FeCo alloy self-supporting electrode, characterized by comprising the following steps:
[0011] (1) Carbon cloth pretreatment: The carbon cloth, which serves as the flexible carbon cloth substrate, is immersed in concentrated nitric acid and treated at 100-140 °C for 8-12 h. After removal, it is washed with deionized water until neutral and dried to obtain hydrophilic carbon cloth.
[0012] (2) Precursor loading: Cobalt nitrate and iron nitrate are dissolved in deionized water to obtain a precursor solution. The hydrophilic carbon cloth is immersed in the precursor solution and the solvent is evaporated at 50-70 °C to load the iron and cobalt precursors onto the surface of the carbon cloth fiber to obtain carbon cloth loaded with precursors.
[0013] (3) In-situ growth: The carbon loaded with the precursor is arranged above a quartz boat containing melamine. Under the protection of flowing nitrogen, the temperature is raised to 600-900 ℃ at a heating rate of 4-6 ℃ / min. After holding at this temperature for 1-2 h, the temperature is cooled so that the carbon and nitrogen-containing species generated by the pyrolysis of melamine can form an in-situ grown nitrogen-doped carbon nanotube array under the catalytic action of iron and cobalt species.
[0014] Further, in step (2), the mass ratio of ferric nitrate to cobalt nitrate is selected from 7:3, 1:1 or 3:7; preferably 3:7.
[0015] Furthermore, in step (3), the mass ratio of melamine to the total mass of cobalt nitrate and ferric nitrate is 15:1 to 40:1.
[0016] Furthermore, in step (3), the temperature is raised to 750°C.
[0017] Another object of the present invention is to provide the application of the above-mentioned bamboo-shaped nitrogen-doped carbon nanotube-coated FeCo alloy self-supporting electrode or the bamboo-shaped nitrogen-doped carbon nanotube-coated FeCo alloy self-supporting electrode prepared by the above preparation method as an air cathode without polymer binder in a rechargeable zinc-air battery.
[0018] Furthermore, the rechargeable zinc-air battery is a liquid zinc-air battery with zinc foil as the anode and 6.0 mol / L KOH aqueous solution as the electrolyte.
[0019] Furthermore, the rechargeable zinc-air battery is a flexible all-solid-state zinc-air battery with zinc sheet as anode and PVA-KOH gel as solid electrolyte.
[0020] Beneficial effects: (1) Nitrogen-doped carbon nanotubes are directly grown on the surface of flexible carbon fiber, and the catalyst layer and the current collector form a continuous conductive integrated structure. This structure does not require polymer binders when used as an air cathode in a zinc-air battery, which helps to reduce additional interfaces and maintain the integrity of the catalyst layer in a bent state.
[0021] (2) The bamboo-like nitrogen-doped carbon nanotubes provide open pores and conductive channels. The FeCo alloy nanoparticles are at least partially coated with a graphitized carbon shell, which helps to limit particle migration and aggregation. XPS characterization confirmed that nitrogen atoms are incorporated into the carbon nanotube lattice in the form of pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen. The three nitrogen species together provide abundant active sites for oxygen reduction and oxygen evolution reactions. The FeCo alloy, nitrogen-containing carbon sites, carbon nanotubes, and carbon cloth substrate together form a solid-liquid-gas mass transfer and electron transport interface.
[0022] (3) When the self-supporting electrode of the present invention is used directly as the air cathode, the peak power density of the liquid zinc-air battery reaches 132.0 mW·cm⁻¹. -2 It also exhibits stable cycling performance exceeding 65 hours; the flexible all-solid-state zinc-air battery has an open-circuit voltage of 1.40V and a peak power density of 127.0 mW·cm⁻¹. -2 It maintains charge and discharge response under bending conditions of 0°, 120° and 180°. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of the preparation process of the FeCo / N-CNTs@CC self-supporting electrode in Example 1 of the present invention.
[0024] Figure 2 The transmission electron microscope characterization results of FeCo / N-CNTs@CC obtained in Example 1 of this invention are shown. The left image shows the bamboo-like nitrogen-doped carbon nanotubes and the particles inside the tubes, while the right image shows the interplanar spacing of the FeCo alloy (110) and the graphitized carbon shell.
[0025] Figure 3 The following are the elemental distribution and phase characterization results of FeCo / N-CNTs@CC obtained in Example 1 of the present invention, wherein (a) is an elemental distribution diagram showing the spatial distribution of C, N, O, Fe and Co, and (b) is an XRD pattern showing the characteristic diffraction peaks of graphitized carbon and FeCo alloy.
[0026] Figure 4 The images show the XPS full spectrum and high-resolution N 1s spectrum of FeCo / N-CNTs@CC obtained in Example 1 of this invention, where (a) is the XPS full spectrum scan and (b) is the high-resolution N 1s spectrum.
[0027] Figure 5 The performance results of the flexible all-solid-state zinc-air battery assembled using the self-supporting electrode of the present invention are shown, where (a) is the polarization curve and power density curve, and (b) is the constant current charge and discharge result under bending conditions of 0°, 120° and 180°.
[0028] Figure 6 ORR linear sweep voltammetric curves are obtained for samples heat-treated at 600 ℃, 700 ℃, 750 ℃, 800 ℃ and 900 ℃, as well as for commercial Pt / C catalysts.
[0029] Figure 7 The ORR linear sweep voltammetric curves are for samples obtained with different ferric nitrate / cobalt nitrate mass ratios.
[0030] Figure 8 The oxygen electrocatalytic performance of FeCo / N-CNTs@CC, control catalyst and carbon cloth obtained in Example 1 of this invention is shown in (a) ORR linear sweep voltammetry curve, (b) OER linear sweep voltammetry curve and (c) overall polarization curve. Detailed Implementation
[0031] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0032] Example 1: Preparation and characterization of FeCo / N-CNTs@CC self-supporting electrode:
[0033] In this embodiment, a self-supporting electrode with bamboo-like nitrogen-doped carbon nanotubes coated on FeCo alloy was prepared, denoted as FeCo / N-CNTs@CC-750. The specific steps are as follows:
[0034] (1) Carbon cloth pretreatment: Carbon cloth (CeTech W0S1009) with a size of 40 mm × 50 mm was immersed in concentrated nitric acid and treated at 120 ℃ for 10 h to improve the hydrophilicity of the carbon cloth surface; after taking it out, it was repeatedly washed with deionized water until neutral and dried at 60 ℃ for later use.
[0035] (2) Precursor loading: Weigh 70 mg cobalt nitrate and 30 mg ferric nitrate, add 50 mL of deionized water and stir until dissolved; immerse the pretreated carbon cloth in the resulting solution, and allow the solvent to evaporate completely at 60 °C, so that the iron and cobalt precursors are loaded onto the surface of the carbon cloth fiber.
[0036] (3) In-situ growth: 2.5 g of melamine was placed in a quartz boat, and the carbon cloth supporting the precursor was placed above the quartz boat and together they were placed in a tube furnace. Under the protection of flowing N2, the temperature was increased from room temperature to 750 ℃ at 5 ℃ / min, held for 1 h and then naturally cooled to room temperature to obtain FeCo / N-CNTs@CC-750 self-supporting electrode.
[0037] The obtained electrodes were characterized by SEM, TEM, HRTEM, EDX, XRD, and XPS. The results showed that nitrogen-doped carbon nanotubes were bamboo-like and grew on the surface of carbon cloth fibers. Most FeCo alloy nanoparticles were located inside the nitrogen-doped carbon nanotubes, while a small number of particles were located on the surface of the carbon cloth. HRTEM showed that the (110) interplanar spacing of the representative FeCo alloy nanoparticles was 0.201 nm, and they were covered with about five layers of graphitized carbon shell. XPS measured the surface nitrogen atom content to be 10.5 atom%, and the N 1s spectrum could be divided into pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen.
[0038] The intrinsic oxygen electrocatalytic performance of the material was tested using a catalyst ink method: FeCo / N-CNTs were scraped from carbon cloth, and 5 mg of the obtained material and 3.8 mg of conductive carbon were added to 1 mL of ethanol and 50 μL of 5% Nafion solution. After ultrasonic dispersion, 12 μL of the mixture was drop-coated onto a glassy carbon electrode. ORR was tested using 0.1 mol / L KOH as the electrolyte, Pt wire as the counter electrode, and an Ag / AgCl electrode as the reference electrode at 1600 rpm and 5 mV / s. The measured ORR onset potential was 0.870 V, half-wave potential was 0.780 V, and limiting current density was 5.63 mA·cm⁻¹. -2 (Potentials are all relative to RHE), the electron transfer number is approximately 3.89. In the OER test, it reaches 10 mA·cm⁻¹. -2 The potential E10 at that time is 1.638 V (relative to RHE), which corresponds to an overpotential of approximately 408 mV relative to a thermodynamic potential of 1.23 V.
[0039] The liquid zinc-air battery uses zinc foil as the anode, intact FeCo / N-CNTs@CC as the polymer-free air cathode, and 6.0 mol / L KOH as the electrolyte, assembled under atmospheric conditions. The current density for the constant current charge-discharge test was 20 mA·cm⁻¹. -2The peak power density of the resulting battery is 132.0 mW·cm⁻¹. -2 It can be stably cycled for more than 65 hours.
[0040] A flexible all-solid-state zinc-air battery uses a zinc sheet as the anode, FeCo / N-CNTs@CC as the air cathode, and PVA-KOH gel as the solid electrolyte. The gel is prepared by adding 5 g of PVA to 50 mL of a 6.0 mol / L KOH solution containing 0.02 mol / L zinc acetate, stirring at 90 °C until homogeneous, forming a film, freezing at −10 °C overnight, and then thawing at room temperature. The resulting flexible battery has an open-circuit voltage of 1.40 V and a peak power density of 127.0 mW·cm⁻¹. -2 ; at 20 mA·cm -2 After 8 hours of cycling, the discharge voltage remained at approximately 1.20 V. When tested at 0°, 120°, and 180°, the voltage gap changes caused by bending were approximately 0, 10, and 5 mV, respectively.
[0041] Example 2: Effect of heat treatment temperature
[0042] Except for setting the heat treatment temperatures in step (3) to 600 ℃, 700 ℃, 800 ℃, and 900 ℃ respectively, the other preparation conditions were the same as in Example 1, and the ORR performance was compared with that of the sample obtained at 750 ℃. The results are shown in Figure 6 The sample obtained at 750 ℃ had the most positive ORR half-wave potential, indicating that among the five temperature conditions investigated, 750 ℃ was more conducive to obtaining higher ORR activity.
[0043] Example 3: Effect of the mass ratio of ferric nitrate to cobalt nitrate
[0044] The mass ratios of ferric nitrate to cobalt nitrate were set to 1:0, 7:3, 1:1, 3:7, and 0:1, respectively, with the remaining preparation conditions the same as in Example 1. The results are shown below. Figure 7 The sample with a feed mass ratio of 3:7 has the most positive ORR half-wave potential and the highest limiting current density among the compared samples. Therefore, 3:7 is determined to be the preferred feed mass ratio under the investigated conditions.
[0045] Comparative Example 1: Commercial precious metal catalysts
[0046] Commercial Pt / C was used as the ORR control catalyst, and commercial RuO2 was used as the OER control catalyst. In addition, an air cathode was prepared with the same Pt / C loading as FeCo / N-CNTs@CC catalyst material for device performance comparison in liquid zinc-air batteries.
[0047] Comparative Example 2: Carbon cloth without catalytic material modification
[0048] Carbon cloth of the same specifications as in Example 1 was used as a substrate control for ORR and OER tests to distinguish the contribution of carbon cloth substrate and FeCo / N-CNTs catalytic material to oxygen electrocatalytic performance.
[0049] In ORR testing, the half-wave potential of FeCo / N-CNTs material was 0.780 V, which is about 35 mV negatively shifted compared to commercial Pt / C, but significantly better than unmodified carbon cloth; in OER testing, FeCo / N-CNTs material reached 10 mA·cm⁻¹. -2 The potential at this time was 1.638 V, close to 1.562 V for RuO2, while the unmodified carbon cloth showed lower activity in the same test range. In the liquid zinc-air battery, the peak power density of the FeCo / N-CNTs@CC air cathode was 132.0 mW·cm⁻¹. -2 130.0 mW·cm⁻¹ with a Pt / C air cathode -2 Comparable; the FeCo / N-CNTs@CC battery cycled stably for more than 65 h, while the discharge voltage of the Pt / C control battery decreased significantly within about 44 h.
Claims
1. A self-supporting electrode of FeCo alloy coated with bamboo-like nitrogen-doped carbon nanotubes, characterized in that, The invention includes a flexible carbon cloth substrate, an array of nitrogen-doped carbon nanotubes grown in situ on the surface of the flexible carbon cloth substrate, and FeCo alloy nanoparticles. The nitrogen-doped carbon nanotubes have a bamboo-like structure, and the FeCo alloy nanoparticles are at least partially encapsulated within the nitrogen-doped carbon nanotubes. The array of nitrogen-doped carbon nanotubes and the flexible carbon cloth substrate together form a continuously conductive self-supporting structure.
2. The self-supporting electrode of FeCo alloy coated with bamboo-like nitrogen-doped carbon nanotubes according to claim 1, characterized in that, At least a portion of the surface of the FeCo alloy nanoparticles is coated with a graphitized carbon shell.
3. The self-supporting electrode of FeCo alloy coated with bamboo-like nitrogen-doped carbon nanotubes according to claim 1, characterized in that, The electrode contains pyridine nitrogen, pyrrole nitrogen and graphitic nitrogen, and the nitrogen atom content on the electrode surface is 8~15 atom.
4. A method for preparing a self-supporting electrode of FeCo alloy coated with bamboo-like nitrogen-doped carbon nanotubes as described in any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Carbon cloth pretreatment: The carbon cloth, which serves as the flexible carbon cloth substrate, is immersed in concentrated nitric acid and treated at 100-140 °C for 8-12 h. After removal, it is washed with deionized water until neutral and dried to obtain hydrophilic carbon cloth. (2) Precursor loading: Cobalt nitrate and iron nitrate are dissolved in deionized water to obtain a precursor solution. The hydrophilic carbon cloth is immersed in the precursor solution and the solvent is evaporated at 50-70 °C to load the iron and cobalt precursors onto the surface of the carbon cloth fiber to obtain carbon cloth loaded with precursors. (3) In-situ growth: The carbon loaded with the precursor is arranged above a quartz boat containing melamine. Under the protection of flowing nitrogen, the temperature is raised to 600-900 ℃ at a heating rate of 4-6 ℃ / min. After holding at this temperature for 1-2 h, the temperature is cooled so that the carbon and nitrogen-containing species generated by the pyrolysis of melamine can form an in-situ grown nitrogen-doped carbon nanotube array under the catalytic action of iron and cobalt species.
5. The preparation method according to claim 4, characterized in that, In step (2), the mass ratio of ferric nitrate to cobalt nitrate is selected from 7:3, 1:1 or 3:7; preferably 3:
7.
6. The preparation method according to claim 4, characterized in that, In step (3), the mass ratio of melamine to the total mass of cobalt nitrate and ferric nitrate is 15:1 to 40:
1.
7. The preparation method according to claim 4, characterized in that, In step (3), the temperature is raised to 750°C.
8. The self-supporting electrode of FeCo alloy with bamboo-like nitrogen-doped carbon nanotubes as described in any one of claims 1 to 3, or the self-supporting electrode of FeCo alloy with bamboo-like nitrogen-doped carbon nanotubes prepared by the preparation method described in any one of claims 4 to 7, as an air cathode without polymer binder in a rechargeable zinc-air battery.
9. The application according to claim 8, characterized in that, The rechargeable zinc-air battery is a liquid zinc-air battery with zinc foil as the anode and 6.0 mol / L KOH aqueous solution as the electrolyte.
10. The application according to claim 8, characterized in that, The rechargeable zinc-air battery is a flexible all-solid-state zinc-air battery with zinc sheet as anode and PVA-KOH gel as solid electrolyte.
